2018
DOI: 10.1111/bju.14562
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the inflammatory response after sclerotherapy for hydrocoele/spermatocoele

Abstract: Objective To investigate the modulation of the inflammatory response after sclerotherapy for hydrocoele/spermatocoele. Patients and Methods All patients with hydrocoele or spermatocoele presenting at the Department of Urology, University Hospital, Linköping, Sweden, from 2006 to 2012, were included in this prospective observational study of sclerotherapy for hydrocoele/spermatocoele using polidocanol as a sclerosing agent and adjuvant antibiotic and anti‐inflammatory medication (AAAM) for modulation of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Rassaam et al, in their case report, concluded that, sclerotherapy was found to be curative and that it should be considered at the early stages of presentation 1 . Jahnson et al and Lund et al, also reported in favor of the management of hydrocele patients with sclerotherapy 16,17 . However, according to Khaniya et al, sclerotherapy had lesser complications as compared to the surgical treatments but it had a lower success rate and less patient satisfaction 18 .…”
Section: Discussionmentioning
confidence: 98%
“…Rassaam et al, in their case report, concluded that, sclerotherapy was found to be curative and that it should be considered at the early stages of presentation 1 . Jahnson et al and Lund et al, also reported in favor of the management of hydrocele patients with sclerotherapy 16,17 . However, according to Khaniya et al, sclerotherapy had lesser complications as compared to the surgical treatments but it had a lower success rate and less patient satisfaction 18 .…”
Section: Discussionmentioning
confidence: 98%